Odpowiedź :
Odpowiedź:
a) x+9=16
x = 16 - 9 = 7
b) 2x+1=17
2x = 16 /:2
x = 8
c) 3x+9=2x+5
3x - 2x = 5 - 9
x = -4
d) x-2=8-4x
5x = 10 /:5
x = 2
e) 2(x+4)-9=5x-4
2x + 8 - 9 = 5x - 4
- 3x = - 3 /:(-3)
x = 1
f) 4x-3(3x-5)=6x-13
4x - 9x + 15 - 6x = -13
- 11 x = - 28
x = [tex]\frac{28}{11}[/tex]
Odpowiedź:
a) x+9=16
x = 16 - 9 = 7
b) 2x+1=17
2x = 16 /:2
x = 8
c) 3x+9=2x+5
3x - 2x = 5 - 9
x = -4
d) x-2=8-4x
5x = 10 /:5
x = 2
e) 2(x+4)-9=5x-4
2x + 8 - 9 = 5x - 4
- 3x = - 3 /:(-3)
x = 1
f) 4x-3(3x-5)=6x-13
4x - 9x + 15 - 6x = -13
- 11 x = - 28
x =
Szczegółowe wyjaśnienie: